PENGARUH PEMBELAJARAN KEWIRAUSAHAAN, PRAKTIK KERJA INDUSTRI, DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP KESIAPAN BERWIRAUSAHA - Lukman Anggriawan; Rusno Rusno; Riril Mardiana Firdaus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
This research aimed to show the influence of entrepreneurship learning, field work industry and entrepreneurship knowledge towards the readiness of doing an entreprenenur. This research use quantitative approach with expo-facto method. The number of population was 126 students at SMK Budi Mulia Pakisaji. The number of sampling was 65 students which is determined by using proportional random sampling. The technique of data collection was using questionnaire. Based on analysis result, it could be concluded; there was an influence of entrepreneurship learning, field work industry and entrepreneurship knowledge towards the readiness of doing an entreprenenur, simultaneously, there was an influence of entrepreneurship learning, field work industry and entrepreneurship knowledge towards the readiness of doing an entreprenenur and R² value amount 0,779% it means that the influence of doing entrepreneurship learning, field work industry and entrepreneurship knowledge amount 77% towards the readiness of doing an entrepreneur.